Robo-pete ebook - Dean, James (Pete the Cat., 2015)
When Pete's friends don't want to play the same games as he does, Pete has a great idea—he'll build a robot that's just like him! But when Robo-Pete gets a little out of control, Pete realizes the best thing about his friends is that no matter what they like to play, it's always fun when they're all together. Don't miss this Pete the Cat storybook by New York Times bestselling artist James Dean!